Muslim consumers’ purchase behavior towards shariah compliant hotels in Malaysia - Haque, A. K. M. Ahasanul; Chowdhury, Naila Anwar; Yasmin, Farzana; Tarofder, Arun Kumar (University of Sri Jayewardenepura, Sri Lanka., 2019)
As the number of Muslim tourists drastically increased, the concept of Shariah Compliant Hotel (SCH) has become a vital concern particularly in Islamic tourism. Shariah compliance is one of the primary aspects that influence Muslim consumers’ choice of accommodation while travelling. For such reason, the present study has been developed to examine the factors that affect Muslim consumers purchase behavior towards Shariah compliant hotels. Henceforth, a conceptual framework has been constructed based on past literature. The primary data were collected from Muslim travelers specifically in Kuala Lumpur, Malaysia using a self-administered questionnaire. Statistical Package for Social Sciences (SPSS) and Structural Equation Modeling (SEM) were employed to analyze data. Based on the results the aspects of halal image, followed by halal awareness along with religiosity have been found to have profound effects on Muslim consumers purchase intention towards Shariah compliant hotels. Further, purchase intention has a significant effect on purchase behavior towards Shariah compliant hotels. The outcomes derived from this research will be of immense importance for destination marketers as well as hoteliers for crafting effective strategies in terms of meeting the needs of Muslim consumers. At the same time, the study would also facilitate future researchers to undertake more studies in Islamic tourism particularly, Shariah compliant hotels.